The relation of autonomic biomarkers to the patient’s outcome with acute coronary syndrome - Abdi, Zana; Hussein, Hishyar MS Garmavy; Rasool, Suzan (Journal of Contemporary Medical Sciences, 2023)
Objectives: This study aimed to evaluate the neurohormonal activity in patients with acute coronary syndrome and their relation to clinical outcomes by measuring plasma chromogranin A and plasma and RBC cholinesterase activity. Methods: In this case-control study, cardiac and neurohormonal parameters were compared between fifty-one patients with acute coronary syndrome admitted to the cardiac center in Azadi teaching Hospital in Duhok-Iraq, and thirty comparable gender and age-healthy subjects. Results: A significant increase in sympathetic activity was reported in patients with the acute coronary syndrome, reflected by the rise in the plasma chromogranin A compared to the control group (994.47 vs. 1203.95 ng/L, respectively, P<0.05). Meanwhile, cardiac troponin was significantly elevated in those patients compared to healthy subjects (0.17 vs. 4.82 ng/ml, respectively). However, the parasympathetic biomarkers (plasma and RBC cholinesterase activity) did not differ substantially between patients and healthy controls (0.83 vs. 0.92, P > 0.05 and 1.36 vs. 1.37, P>0.05, respectively). Serum troponin I was more valid than chromogranin A in differentiating acute coronary syndrome from healthy subjects. The area under the curve for troponin I was (0.989) compared to ( 0.724) for chromogranin A. Furthermore, plasma chromogranin A but not plasma and RBC cholinesterase activity was significantly increased in fatal cases compared to nonfatal patients (1166.68 vs. 3435.64 ng/L). Conclusion: Plasma chromogranin A was less effective than troponin I in detecting acute coronary cases; however, it can be helpful as a prognostic marker in those patients. Parasympathetic biomarkers were not appreciable in diagnosing and detecting risky patients.